ASPECTOS ECOLÓGICOS DE DUAS GRANDES COLÔNIAS DE MORCEGOS NECTARÍVOROS (ANOURA GEOFFROYI GRAY, 1838) RESIDENTES EM CAVERNAS NO BRASIL: IMPLICAÇÕES PARA CONSERVAÇÃO - Reis, Aline da Silva (2022)
Bats of the Anoura geoffroyi species have a wide distribution in the Neotropics, occurring in North, Central and South America. The formation of large colonies enhances the important ecological role developed by the species in the pollination of a wide variety of plants. In this work a concomitant study in two colonies of Anoura geoffroyi was conducted, emphasizing the structure and population dynamics of the species. These colonies are located in one of the main regions of mineral interest in Brazil, the Iron Quadrangle, state of Minas Gerais. It was observed that the colonies represent large populations with a marked variation in population density throughout the year and may aggregate thousands of individuals during the early reproductive period. Both colonies showed sexual segregation behavior with the shelters occupied mostly by males in the first months of the year. Females arrive in the caves for mating at the peak of the dry season. They remain in the shelter until nearly the end of gestation, leaving the studied caves in early summer where they seek another shelter (maternity colony) for the completion of gestation (birth) and subsequent care of the offspring. Therefore, it was concluded that the intrinsic characteristics of the natural history of the species have important implications for its conservation, since the preservation of diurnal shelters is closely related to the reproductive cycle of the species. In turn, the current Brazilian legislation allows the suppression of natural underground cavities based on studies that, depending on the sampling period, may be insufficient to detect the use of these essential shelters for the completion of the reproductive cycle of species. These that are considered relatively common, with a fundamental ecosystem role for epigeal and underground environments, and which are not on the official lists of endangered species.